Sleep Patterns and Quality in Omani Adults - Al-Abri MA (Dove Medical Press, 2020)
Mohammed A Al-Abri,1 Ibtisam Al lawati,2 Fahad Zadjali,3 Shyam Ganguly4 1Department of Physiology, College of Medicine and Health Sciences, Sultan Qaboos University, Muscat, Sultanate of Oman; 2Department of Physiology, Oman College of Health Sciences, Muscat, Sultanate of Oman; 3Department of Biochemistry, College of Medicine and Health Sciences, Sultan Qaboos University, Muscat, Sultanate of Oman; 4Department of Family Medicine and Public Health, College of Medicine and Health Sciences, Sultan Qaboos University, Muscat, Sultanate of OmanCorrespondence: Mohammed A Al-AbriDepartment of Physiology, College of Medicine and Health Sciences, Sultan Qaboos University Hospital, Al-Khoud 123, P.O. Box 38, Muscat, Sultanate of OmanTel +968 24144702Email malabri@squ.edu.omBackground: Sleep patterns have changed continuously worldwide and it can be influenced by social, cultural, and environmental factors. These patterns may be associated with poor sleep quality and daytime sleepiness. The aim of the study was to investigate sleep patterns and quality in Omani adults using actigraphy.Subjects and Methods: This was a cross-sectional study conducted between June 2015 and February 2017. Four hundred subjects agreed to participate in the study (52% male, 48% female). Subjects were randomly selected and enrolled in the study among young adults and middle aged individuals living in the City of Muscat. Subjects were asked to fill-in Epworth sleepiness scale (ESS) and Pittsburgh sleep quality index (PSQI). Actigraphy was used to measure their sleep patterns for one week.Results: The mean age of participants was 32.80± 11.50 years. Four sleep patterns were identified: monophasic, bi-phasic (post-dawn), bi-phasic (afternoon siesta), and polyphasic (three sleep periods/24 hours). The study revealed that 35% of participants had biphasic-siesta sleep pattern, 28% polyphasic, 26% monophasic, and 11% biphasic-dawn. The biphasic siesta pattern was found to be associated with younger age group (25– 34 years) (P=0.001). Polyphasic sleep was associated with higher ESS score (P=0.001) but not with poor sleep quality (P=0.24). There was no significant difference in night sleep duration among all the sleep patterns (P=0.07) but the polyphasic sleep pattern had higher total 24-hour day sleep duration (P=0.03). Nearly 90% of participants practiced afternoon siestas with mean duration of 45± 43 minutes.Conclusion: The predominant sleep pattern among Omanis was biphasic-siesta and majority of people practiced afternoon siesta. Polyphasic sleep pattern is associated with daytime sleepiness.Keywords: sleep patterns, sleepiness, siesta, polyphasic, fragmented sleep